A Phase I/ II Feasibility Study of Intravenous Cetuximab in Combination with 5 days Weekly Oral Capecitabine and Preoperative Radiotherapy in Rectal Cancer (XERXES) - Glynne-Jones, Robert; Meadows, Helen M; Lopes, Andre; Riddle, Pippa; Duggan, Marian; Sebag-Montefiore, David; McDonald, Alec; Samuel, Les; Falk, Stephen; Adams, Richard (Archives of Clinical and Biomedical Research, 2020)
Background Preoperative Long-course chemoradiation (LCCRT) is the standard-of-care in locally advanced rectal cancer (LARC). This phase I/II trial in two sequential studies aimed to evaluate the activity and safety of the anti-epidermal growth factor receptor (EGFR) monoclonal antibody cetuximab administered weekly-prior to, and following LCCRT. Patients and Methods All patients had magnetic resonance imaging (MRI) defined cT3/cT4 or node-positive rectal adenocarcinoma and treatment with LCCRT (capecitabine 825 mg/m2 bid on Monday-Friday for 5 weeks during radiotherapy [45Gy in 25 daily fractions] followed by total mesorectal excision (TME). In Phase I patients received weekly induction cetuximab 400mg/m2 loading, then 250mg/m2 once weekly for 4 weeks prior to standard LCCRT. In phase II 10 patients were randomised to receive: arm A standard LCCRT alone or arm B (sandwich) LCCRT with additional induction cetuximab 250mg/m2 weekly prior to LCCRT and consolidation for 5 weeks following. Results In Phase I all 12 patients proceeded to surgery with a single pCR (8%) reported. This pCR rate together with acceptable compliance (100%) and toxicity (4 Grade 3 toxicities, 2 skin rash, 1 pain and 1 pulmonary embolus) and the absence of severe surgical complications allowed continuation to phase II. In Phase II, 10 patients were recruited and five patients were randomly assigned to each treatment arm. One additional patient allocated cetuximab/CRT chose to withdraw from the trial and received no treatment. In Arm B 4/5 patients proceeded to surgery with one pCR compared to three of five patients proceeding to surgery with two achieving pCR in Arm A. The Trial closed after studies in metastatic disease reported efficacy depended on selection according to K-RAS/NRAs mutational status. Conclusions: In unselected pati